Filamin A Phosphorylation at Serine 2152 by the Serine/Threonine Kinase Ndr2 Controls TCR-Induced LFA-1 Activation in T Cells - Waldt, Natalie; Seifert, Anke; Demiray, Yunus Emre; Devroe, Eric; Turk, Benjamin E.; Reichardt, Peter; Mix, Charlie; Reinhold, Annegret; Freund, Christian; Müller, Andreas J.; Schraven, Burkhart; Stork, Oliver; et al. (Frontiers in Immunology, 2018)
The integrin LFA-1 (CD11a/CD18) plays a critical role in the interaction of T cells with antigen presenting cells (APCs) to promote lymphocyte differentiation and proliferation. This integrin can be present either in a closed or in an open active conformation and its activation upon T-cell receptor (TCR) stimulation is a critical step to allow interaction with APCs. In this study we demonstrate that the serine/threonine kinase Ndr2 is critically involved in the initiation of TCR-mediated LFA-1 activation (open conformation) in T cells. Ndr2 itself becomes activated upon TCR stimulation and phosphorylates the intracellular integrin binding partner Filamin A (FLNa) at serine 2152. This phosphorylation promotes the dissociation of FLNa from LFA-1, allowing for a subsequent association of Talin and Kindlin-3 which both stabilize the open conformation of LFA-1. Our data suggest that Ndr2 activation is a crucial step to initiate TCR-mediated LFA-1 activation in T cells.